2022
DOI: 10.1038/s41586-021-04255-y
|View full text |Cite
|
Sign up to set email alerts
|

The size of the land carbon sink in China

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 13 publications
1
51
0
1
Order By: Relevance
“…A recent atmospheric inversion-based study reported that China’s land ecosystems were a large CO 2 sink of −1.11 ± 0.38 Pg C per year 27 , which seems to be ecologically implausible and critically sensitive to the assimilation of the CO 2 record from one station 28 . The compilation of previous studies from inventory- and satellite-based estimation, atmospheric inversion, and process-based models suggested that the Chinese C sink was much smaller (−0.18– −0.45 Pg C per year; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent atmospheric inversion-based study reported that China’s land ecosystems were a large CO 2 sink of −1.11 ± 0.38 Pg C per year 27 , which seems to be ecologically implausible and critically sensitive to the assimilation of the CO 2 record from one station 28 . The compilation of previous studies from inventory- and satellite-based estimation, atmospheric inversion, and process-based models suggested that the Chinese C sink was much smaller (−0.18– −0.45 Pg C per year; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier assessments of the LUCC impact differed among regions, time periods, and biomes [12][13][14] . For example, LUCC-induced cumulative C emission in China may differ by a factor of three to five according to different studies (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) Pg C vs 6.18 Pg C from 1700 to 2000) based on similar bookkeeping models 12,14 . Such discrepancies mainly stem from the use of different LUCC data 14 .…”
mentioning
confidence: 99%
“…1a), counterbalancing 8% of the mean annual fossil CO 2 emissions in the same period (7.5 PgCO 2 yr −1 ), in which the increased carbon sequestration from ecosystems (0.5 PgCO 2 yr −1 , excluding CH 4 and N 2 O) is about 54% (28-80%) of the overall land carbon sink in China (0.18-0.51 PgC yr −1 ) (ref. 10 ). During 2020-2030, the maximum potential of NCS (MAMP) of the 16 pathways is projected at 0.6 (0.3-1.0) PgCO 2 e yr −1 (Fig.…”
Section: Overall Ncs Potentialmentioning
confidence: 99%
“…Climate and Atmosphere Research Center (CARE-C), The Cyprus Institute, Nicosia, Cyprus. 10 Institute of Biological and Environmental Sciences, University of Aberdeen, Aberdeen, UK. ✉ e-mail: bfu@rcees.ac.cn N atural climate solutions (NCS), a suite of land-management options including protecting, restoring and sustainably managing ecosystems 1 , provide readily implementable approaches to sequester carbon in terrestrial pools and/or reduce GHG emissions 2 .…”
mentioning
confidence: 99%
“…As mentioned above, most atmospheric inversion studies use midday CO 2 observations to constrain local anthropogenic CO 2 emissions because the midday PBL is typically well-mixed compared to at night. Further, the aggregation (or representation) error is also minimum at midday than at night with stable nocturnal conditions ( Wang et al, 2022 ). Because the transport uncertainty is relatively small compared to that at night we have used the midday observations to constrain CO 2 emissions (see highlighted bold lines in Fig.…”
Section: Resultsmentioning
confidence: 99%